Association between urinary metals and leukocyte telomere length involving an artificial neural network prediction: Findings based on NHANES 1999–2002 - Xia, Fang; Li, Qingwen; Luo, Xin; Wu, Jinyi (Frontiers in Public Health, 2022)
Objective Leukocytes telomere length (LTL) was reported to be associated with cellular aging and aging related disease. Urine metal also might accelerate the development of aging related disease. We conducted this research to explore the association between urine metals and LTL, and further make a practical prediction of LTL. Methods In this research, we screened all cycles of National Health and Nutrition Examination Survey (NHANES) dataset, and download the eligible datasets in NHANES 1999-2002 containing demographic, disease history, urine metal and leukocyte telomere length. The analysis in this research had 3 steps including baseline data difference comparison, multivariate linear regression (MLR) for hazardous urine metals associated with LTL, and artificial neural network (ANN, based on tensorflow framework) to make LTL prediction based on all the variables included. Results The MLR results showed that urinary cadmium (Cd), cobalt (Co) and antimony (Sb) were negatively correlated with LTL in the USA elderly population, urinary cesium (Cs) and molybdenum (Mo) were positively correlated with LTL. The relationship between urinary lead (Pb) and LTL remained controversial, while no correlations were found between urinary thallium (Tl), barium (Ba) and LTL. There were few previous studies about Cs and Mo with LTL and some neonatal studies reported that Tl and Ba were related with the shortening of LTL. Conclusions Several urinary metals including Cd, Sb, Cs, Mo, Co and Pb had association with LTL. Moreover, in adults especially the elderly, the relationships between urinary Cs, Mo, Tl, Ba and LTL might be worthy of further research.